IMPLEMENTASI KEBIJAKAN BATAS DESA RATATOTOK-BUYAT PROVINSI SULAWESI UTARA - SUMAHAF, LINDA MARLINA NOVELIA; TAMPI, GUSTAAF BUDI; RURU, JOORIE (Sam Ratulangi University, 2020)
study aims to determine the implementation of the policy of the village of Ratatotok-Buyat inthe North Sulawesi Province. The theory used in this research is the theory of policy implementationproposed by Edward III: communication, resources, disposition, and bureaucratic structure. This type ofresearch is descriptive qualitative. There are 10 people used as informants in this study and to collect dataand search for research data using interviews in this study, after the data are collected and will beanalyzed descriptively, in order to get answers about the implementation of the Rataotok-Buyat villageboundary policy. After conducting in-depth research and interviews, the results of research on theimplementation of the Ratatotok-Buyat village boundary policy in North Sulawesi Province, namely thecommunication process that occurs in the implementation of the Ratatotok-Buyat village boundary policyto the support of human resources in implementing the Ratatotok-Buyat village boundary policy Thispolicy implementation was not well realized. The regional government needs to re-socialize the Ratatotok-Buyat village boundary policy as stipulated in Permendagri No. 69 of 2016 and the government is evenmore transparent in every policy issued.Ke Words: Policy Implementation, village boundaries